(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The article deals with the problems of the construction waste formed in the course of demolition and construction of buildings in the city. The author presents results of investigations of construction sites located on the territory of Samara, gives the analysis of the construction waste composition and considers options for the use of the construction waste as a secondary resource in the manufacture of building materials.